SIMULATION OF IMPACT PROCESS OF SOIL COMPACTION - R. A. Chukharev; N. E. Tarasova; E. K. Chabutkin (Вестник СибАДИ, 2020)
Introduction. During the construction of modern highways, much attention is paid to compaction of bases consisting of natural soils. They require the use of special equipment, including self-propelled machines, performing compaction in a continuous cycle. But when designing it, certain difficulties arise in determining the parameters of impact accelerators and the mass of the impact plate. The purpose of the work is to study the influence of the parameters of working equipment on the process of soil deformation.Materials and methods. To check the influence of the parameters of the tamper equipment on the compaction process, a method of mathematical modeling of the process using rheological models was chosen. The working cycle of impact ramming is divided into four phases. A mathematical description of the movement of the stamp and soil in each of the phases of movement is given. The change in the stress condition in time in the body of the soil half-space is considered.Results.Тhe time dependence of the soil stress condition was obtained for different stiffnesses of the spring impact accelerator and the change in the stamp mass. A joint analysis of the obtained dependencies showed that when designing impact equipment intended for compaction of naturally occurring soils, it requires matching the peak stresses from the mass of the stamp and the stiffness of the impact accelerators. This will make it possible to stretch the action of stresses in time, to form a compacted core in the soil half-space quickly and require a smaller number of strokes on one track to obtain the required material density.Discussion and conclusion. The proposed model of tamper equipment made it possible to consider the processes occurring in the soil half-space, to obtain comparative characteristics of the stamp mass and the rigidity of impact accelerators. The obtained data correlate well with the data of other authors. The results of the study may be useful to engineers involved in the development of new techniques of intensifying action.Financial transparency: the authors have no financial interest in the presented materials or methods. There is no conflict of interest.